An Adjustment Method for the Suspender Tension of CFSTTTHAB Based on Influence Matrix of Single Suspender - Longlin Wang; Hua Wang; Litao Li; Tianzhi Hao; Changxia Wu (Advances in Civil Engineering)
Based on the funding project “a concrete-filled steel tube truss type half-through arch bridge (CFSTTTHAB) with the span of 220 m,” in view of the difference of tension between one pair of suspenders, this paper proposed an improved influence matrix method for the tension of a single suspender, which was developed from a conventional influence matrix. A method for adjusting suspender tension at the completed state of construction by using numerical simulation and iterative algorithm was also presented. Finite element numerical model was used to calculate the influence matrix of a single suspender. Moreover, an iterative algorithm was used to solve the adjustment value of suspender tension. Based on the proposed method, by processing several iterations, the difference between the measured and designed suspender tension would be controlled within 6% in the projects of suspender tension adjustment. Finally, the comparison between the measured and designed suspender tension at the completed state of construction proved the feasibility and accuracy satisfaction of the proposed method for engineering requirement.